PERBANDINGAN ANTARA LOADING CAIRAN KOLOID DENGAN PRETREATMENT FENILEFRIN TERHADAP WAKTU TERJADINYA PENURUNAN TEKANAN DARAH PADA PASIEN GERIATRIK DENGAN BLOK SUBARAKHNOID - Santoso, Fabri Drajat; S, Gaus; A, Adil; A, Salahuddin; F, Muchtar; H, Nurdin (E-Jurnal Medika Udayana, 2025)
Background: Subarachnoid block provides the possibility of complications in geriatric patients, one of which is hypotension. This study aims to compare colloid fluid loading with phenylephrine pretreatment on the reduction in blood pressure after BSA. Methods: This study was a double-blind, randomized clinical trial carried out at Wahidin Sudirohusodo General Hospital and educational network hospitals in Makassar from January to April 2024. Patients were divided into two groups: patients who received colloid loading and patients who received phenylephrine premedication. Results: A total of 48 patients took part in the study and were divided equally into two groups. It was found that the mean arterial pressure value was highest in the phenylephrine group compared to colloid, namely at 5, 6, 7, 8, and 12 minutes (p<0.05). The frequency of hypotension and onset of hypotension between the two groups showed statistically significant differences (frequency: p = 0.041; onset: p = 0.044), where the frequency of hypotension in the phenylephrine group was less and the average onset of hypotension in the phenylephrine group was also longer, namely amounting to 7.20 minutes. Conclusion: Phenylephrine pretreatment can prevent hypotension better than colloid loading.